Anti-aging PVC material

By adding specific components to the PVC material, the polyvinyl chloride resin matrix is ​​induced to form silver patterns and enhance anti-oxidation and thermal aging properties, the problem of lack of toughness and anti-aging properties of PVC materials is solved, and higher toughness and anti-aging effects are achieved.

CN119684725APending Publication Date: 2025-03-25PUNING YONMEILE PLASTIC PROD CO LTD

Patent Information

Application Number
CN202411952445.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The lack of toughness and anti-aging properties of existing PVC materials leads to hardening and embrittlement during long-term use, reducing the reliability and service life of the product.

Method used

By adding hydrotalcite, polyoxyethylene sorbitan monooleate, sodium 4-n-octylbenzene sulfonate, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone and trihydroxymethylaminomethane to the raw materials of the PVC material, the polyvinyl chloride resin matrix is ​​induced to form silver patterns, absorb impact energy, and enhance the toughness and anti-aging properties of the material through multiple angles of antioxidant, ultraviolet light conversion and thermal aging.

Benefits of technology

It significantly improves the toughness and anti-aging properties of PVC materials, extends service life, and provides higher safety guarantees.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215165230000021
    Figure BDA0005215165230000021
  • Figure BDA0005215165230000041
    Figure BDA0005215165230000041
  • Figure BDA0005215165230000051
    Figure BDA0005215165230000051
Patent Text Reader

Abstract

The invention relates to an anti-aging PVC material, and belongs to the technical field of PVC material preparation, the anti-aging PVC material comprises the following raw materials: polyvinyl chloride resin, hydrotalcite, polyoxyethylene sorbitan monooleate, 4-n-octyl sodium benzenesulfonate, 4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4' The invention relates to a high-temperature-resistant anti-rust paint which is prepared from the following raw materials: 4, 4 '-thiobis (6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone, trihydroxymethyl aminomethane, dicumyl peroxide and stearic acid. The hydrotalcite, the polyoxyethylene sorbitan monooleate and the sodium 4-n-octylbenzenesulfonate are added into the raw materials, so that the toughness of the finished PVC material is enhanced; by adding 4, 4 '-thiobis (6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone and trihydroxymethyl aminomethane, the anti-aging performance of the finished product is synergistically improved from multiple angles of oxidation resistance, ultraviolet light conversion and thermal aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC material preparation, and in particular relates to an anti-aging PVC material. Background Art

[0002] PVC is the abbreviation of polyvinyl chloride material. It is a material made of polyvinyl chloride resin as the main raw material, with other appropriate additives added through mixing, calendering and other processes. It is widely used in various fields. Although PVC materials are widely used, materials with poor aging resistance will gradually harden and become brittle during long-term use, reducing the reliability and service life of the product. Although there are many PVC materials on the market, the PVC materials on the market lack toughness and aging resistance, which seriously affects the customer's experience. Therefore, providing a PVC material with excellent toughness and aging resistance is of great significance to meet industry needs, extend service life and provide safety guarantees. Summary of the invention

[0003] The invention aims to provide an anti-aging PVC material. By adding hydrotalcite to the raw materials, when the composite material is subjected to impact, silver streaks are induced in a polyvinyl chloride resin matrix to absorb impact energy, become a stress concentrator, and play a toughening role. On this basis, polyoxyethylene sorbitan monooleate and sodium 4-n-octylbenzenesulfonate are added to further consolidate and strengthen the toughness of the finished PVC material. In addition, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone and trishydroxymethylaminomethane are added. The three are started from multiple angles of anti-oxidation, ultraviolet light conversion and heat aging resistance, and the anti-aging performance of the finished product is synergistically increased. The problem of the lack of toughness and anti-aging performance of the PVC material in the prior art is solved.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] An anti-aging PVC material, comprising the following raw materials in parts by weight:

[0006]

[0007] As a preferred embodiment of the present invention, the anti-aging PVC material further comprises 80-100 parts by weight of deionized water and 80-90 parts by weight of anhydrous ethanol.

[0008] As a preferred embodiment of the present invention, the method for preparing the anti-aging PVC material comprises the following steps:

[0009] S10, pre-treating part of the raw materials to obtain mixed solution A and mixed solution B for standby use;

[0010] S20, preparing pre-treatment material;

[0011] S30, preparing anti-aging PVC material.

[0012] As a preferred solution of the present invention, the specific steps of step S10 are:

[0013] S11, mixing polyoxyethylene sorbitan monooleate and sodium 4-n-octylbenzenesulfonate and stirring evenly to obtain a mixed solution A for standby use;

[0014] S12, stirring the hydrotalcite, anhydrous ethanol and deionized water in a water bath to obtain a mixed solution B for standby use.

[0015] As a preferred embodiment of the present invention, the temperature of the water bath in step S12 is 75-80° C.; and the stirring time is 30-50 min.

[0016] As a preferred embodiment of the present invention, the specific steps of step S20 are: mixing the mixed solution A and the mixed solution B evenly and stirring them in an oil bath, and after the stirring is completed, filtering, washing and drying are performed to obtain a pre-treated material.

[0017] As a preferred embodiment of the present invention, the temperature is 80-85° C., and the stirring time is 30-40 min.

[0018] As a preferred embodiment of the present invention, the specific steps of step S30 are: polyvinyl chloride resin, diisopropylbenzene peroxide, pre-treated material, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone, tris(hydroxymethylaminomethane) and stearic acid are mixed in a double-roll mill under temperature control to form a PVC finished sheet, which is an anti-aging PVC material.

[0019] As a preferred solution of the present invention, the temperature of the temperature control is 160-170° C.; the mixing time is 5-7 min; and the thickness of the finished PVC sheet is 0.5-0.6 mm.

[0020] As a preferred embodiment of the present invention, the roller of the twin-roll mill is 350 mm long and 120 mm in diameter, and is heated by oil. The rotation speeds of the front and rear rollers are 25 rpm and 30 rpm respectively.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention adds hydrotalcite. When the composite material is subjected to impact, it induces the polyvinyl chloride resin matrix to form silver streaks, absorbs impact energy, becomes a stress concentrator, and plays a toughening role. On this basis, polyoxyethylene sorbitan monooleate is added to increase the steric hindrance of the hydrotalcite, and sodium 4-n-octylbenzenesulfonate further reacts with the hydrotalcite to form a charged adsorption layer. The hydrotalcite particles in the system achieve a uniform and stable dispersion state through electrostatic repulsion, further consolidating and strengthening the toughness of the finished PVC material.

[0023] (2) The present invention adds 4,4'-thiobis(6-tert-butyl-3-methylphenol) with less steric hindrance and greater hydroxyl activity. When it participates in the antioxidant effect, its hydroxyl group will react with the polymer peroxyl radical, and the sulfur atom can decompose the hydroperoxide to stabilize the polymer and play an antioxidant role; through the conversion of the conjugated bonds in 2-hydroxy-4-n-octyloxybenzophenone, ultraviolet light is converted into harmless energy such as fluorescence, thereby releasing the PVC composite material; at the same time, tris(hydroxymethylaminomethane) reacts with the unstable chlorine atoms on the polyvinyl chloride resin molecular chain to improve the stability of the polyvinyl chloride resin molecular chain. Since the basic groups contained in tris(hydroxymethylaminomethane) can neutralize the release substances during the thermal degradation process of the PVC composite material, the heat aging resistance is increased. That is, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-octyloxybenzophenone and tris(hydroxymethyl)aminomethane synergistically increase the anti-aging performance of the finished product from multiple angles of anti-oxidation, ultraviolet light conversion and anti-thermal aging. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] An anti-aging PVC material, comprising the following raw materials in parts by weight:

[0027]

[0028]

[0029] The preparation method of the anti-aging PVC material comprises the following steps:

[0030] S10, pre-treating part of the raw materials to obtain mixed solution A and mixed solution B for standby use:

[0031] S11, mixing polyoxyethylene sorbitan monooleate and sodium 4-n-octylbenzenesulfonate and stirring evenly to obtain a mixed solution A for standby use;

[0032] S12. Stir the hydrotalcite, anhydrous ethanol and deionized water in a water bath at 75° C. for 40 min to obtain a mixed solution B for later use.

[0033] S20, preparing a pre-treated material: mixing the mixed solution A and the mixed solution B evenly and stirring them in an oil bath at 85° C. for 30 min. After the stirring is completed, filtering, washing and drying are performed to obtain a pre-treated material;

[0034] S30, preparing an anti-aging PVC material: polyvinyl chloride resin, diisopropylbenzene peroxide, pre-treated material, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone, tris(hydroxymethylaminomethane) and stearic acid are mixed in a double-roll mill at a temperature of 170° C. for 5 min to form a PVC finished sheet with a thickness of 0.5 mm, i.e., an anti-aging PVC material;

[0035] The roller of the double-roll mill is 350 mm long and 120 mm in diameter. It is heated by oil, and the rotation speeds of the front and rear rollers are 25 rpm and 30 rpm respectively.

[0036] Example 2

[0037] An anti-aging PVC material, comprising the following raw materials in parts by weight:

[0038]

[0039]

[0040] The preparation method of the anti-aging PVC material comprises the following steps:

[0041] S10, pre-treating part of the raw materials to obtain mixed solution A and mixed solution B for standby use:

[0042] S11, mixing polyoxyethylene sorbitan monooleate and sodium 4-n-octylbenzenesulfonate and stirring evenly to obtain a mixed solution A for standby use;

[0043] S12. Stir the hydrotalcite, anhydrous ethanol and deionized water in a water bath at 78° C. for 30 min to obtain a mixed solution B for later use.

[0044] S20, preparing a pre-treated material: mixing the mixed solution A and the mixed solution B evenly and stirring them in an oil bath at 80° C. for 40 minutes, and after the stirring is completed, filtering, washing and drying to obtain a pre-treated material;

[0045] S30, preparing an anti-aging PVC material: polyvinyl chloride resin, diisopropylbenzene peroxide, pre-treated material, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone, tris(hydroxymethylaminomethane) and stearic acid are mixed in a double-roll mill at a temperature of 165° C. for 7 min to form a PVC finished sheet with a thickness of 0.6 mm, i.e., an anti-aging PVC material;

[0046] The roller of the double-roll mill is 350 mm long and 120 mm in diameter. It is heated by oil, and the rotation speeds of the front and rear rollers are 25 rpm and 30 rpm respectively.

[0047] Example 3

[0048] An anti-aging PVC material, comprising the following raw materials in parts by weight:

[0049]

[0050] The preparation method of the anti-aging PVC material comprises the following steps:

[0051] S10, pre-treating part of the raw materials to obtain mixed solution A and mixed solution B for standby use:

[0052] S11, mixing polyoxyethylene sorbitan monooleate and sodium 4-n-octylbenzenesulfonate and stirring evenly to obtain a mixed solution A for standby use;

[0053] S12. Stir the hydrotalcite, anhydrous ethanol and deionized water in a water bath at 80° C. for 50 min to obtain a mixed solution B for later use.

[0054] S20, preparing a pre-treated material: mixing the mixed solution A and the mixed solution B evenly and stirring them in an oil bath at 83° C. for 35 minutes, and after the stirring is completed, filtering, washing and drying to obtain a pre-treated material;

[0055] S30, preparing an anti-aging PVC material: polyvinyl chloride resin, diisopropylbenzene peroxide, pre-treated material, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone, tris(hydroxymethylaminomethane) and stearic acid are mixed in a double-roll mill at a temperature of 160° C. for 6 min to form a PVC finished sheet with a thickness of 0.6 mm, which is an anti-aging PVC material;

[0056] The roller of the double-roll mill is 350 mm long and 120 mm in diameter. It is heated by oil, and the rotation speeds of the front and rear rollers are 25 rpm and 30 rpm respectively.

[0057] Comparative Example 1

[0058] Compared with Example 1, the difference is that no hydrotalcite is added in Comparative Example 1, and the other parameters and operating steps remain unchanged.

[0059] Comparative Example 2

[0060] Compared with Example 1, the difference is that in Comparative Example 2, polyoxyethylene sorbitan monooleate is not added, and the other parameters and operating steps remain unchanged.

[0061] Comparative Example 3

[0062] Compared with Example 1, the difference is that in Comparative Example 3, no sodium 4-n-octylbenzenesulfonate is added, and the other parameters and operating steps remain unchanged.

[0063] Comparative Examples 4-6

[0064] Compared with Example 3, the difference is that the weight parts of 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone and tris(hydroxymethylaminomethane) in Comparative Examples 4-6 are as shown in Table 1, and the other parameters and operating steps remain unchanged.

[0065] Table 1

[0066]

[0067] Performance Testing

[0068] (1) Toughness test: The anti-aging PVC materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to cantilever beam impact strength test. Impact strength refers to the energy absorbed by a unit cross-sectional area when a sample is broken or fractured under the action of an impact load, which can be used to characterize the toughness of a material. According to the provisions of GB / T 1843-2008 "Determination of cantilever beam impact strength of plastics", the performance of the samples at room temperature and at -20°C for 7 days were tested, and the results are shown in Table 2.

[0069] (2) Tensile strength and anti-aging test: The anti-aging PVC materials prepared in Examples 1-3 and Comparative Examples 4-6 were subjected to a tensile strength test according to GB / T 1040-2006. The results are shown in Table 2.

[0070] At the same time, the samples after the tensile strength test were exposed to outdoor light for 90 days, and then their tensile strength performance was tested, and their tensile strength retention rate was calculated to characterize the anti-aging performance of the material. The higher the tensile strength retention rate, the better the anti-aging performance. The tensile strength retention rate calculation formula is as follows:

[0071] Tensile strength retention rate (%) = tensile strength after irradiation / tensile strength before irradiation × 100%;

[0072] The results are shown in Table 2.

[0073] Table 2

[0074]

[0075]

[0076] It can be seen from Table 2 that the anti-aging PVC material product prepared by the present invention has excellent toughness. Specifically, it can be seen from the data of Examples 1-3 and Comparative Examples 1-3 that the present invention adds hydrotalcite, and when the composite material is subjected to impact, it induces the polyvinyl chloride resin matrix to form silver streaks, absorbs impact energy, becomes a stress concentrator, and plays a toughening role. On this basis, polyoxyethylene sorbitan monooleate is added to increase the steric hindrance of the hydrotalcite, and 4-n-octylbenzenesulfonate is further used to react with the hydrotalcite to form a charged adsorption layer. The hydrotalcite particles in the system achieve a uniform and stable dispersion state through electrostatic repulsion, further consolidating and strengthening the toughness of the finished PVC material.

[0077] It can be seen from the data of Examples 1-3 and Comparative Examples 4-6 that the anti-aging PVC material products prepared by the present invention have outstanding anti-aging performance. This is because the present invention adds 4,4'-thiobis(6-tert-butyl-3-methylphenol) with less steric hindrance and greater hydroxyl activity to play an antioxidant role; 2-hydroxy-4-n-octyloxybenzophenone is added to convert ultraviolet light into harmless energy similar to fluorescence, thereby releasing the PVC composite material; tris(hydroxymethylaminomethane) is added to improve the stability of the polyvinyl chloride resin molecular chain and increase the heat aging resistance; that is, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone and tris(hydroxymethylaminomethane) synergistically increase the anti-aging performance of the finished product from multiple angles of anti-oxidation, ultraviolet light conversion and heat aging resistance.

[0078] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An anti-aging PVC material, characterized in that: The anti-aging PVC material comprises the following raw materials in parts by weight:

2. The anti-aging PVC material according to claim 1, characterized in that: The anti-aging PVC material also includes 80-100 parts by weight of deionized water and 80-90 parts by weight of anhydrous ethanol.

3. A method for preparing the anti-aging PVC material according to claim 2, characterized in that: The preparation method of the anti-aging PVC material comprises the following steps: S10, pre-treating part of the raw materials to obtain mixed solution A and mixed solution B for standby use; S20, preparing pre-treatment material; S30, preparing anti-aging PVC material.

4. The method for preparing an anti-aging PVC material according to claim 3, characterized in that: The specific steps of step S10 are: S11, mixing polyoxyethylene sorbitan monooleate and sodium 4-n-octylbenzenesulfonate and stirring evenly to obtain a mixed solution A for standby use; S12, stirring the hydrotalcite, anhydrous ethanol and deionized water in a water bath to obtain a mixed solution B for standby use.

5. The method for preparing an anti-aging PVC material according to claim 4, characterized in that: In step S12, the temperature of the water bath is 75-80° C.; the stirring time is 30-50 min.

6. The method for preparing an anti-aging PVC material according to claim 3, characterized in that: The specific steps of step S20 are: mixing the mixed solution A and the mixed solution B evenly and stirring them in an oil bath, and after the stirring is completed, filtering, washing and drying to obtain a pre-treated material.

7. The method for preparing an anti-aging PVC material according to claim 6, characterized in that: The temperature of the oil bath is 80-85° C., and the stirring time is 30-40 min.

8. The method for preparing an anti-aging PVC material according to claim 3, characterized in that: The specific steps of step S30 are: mixing polyvinyl chloride resin, diisopropylbenzene peroxide, pre-treated material, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 2-hydroxy-4-n-octyloxybenzophenone, tris(hydroxymethylaminomethane) and stearic acid in a double-roll mill under temperature control to form a finished PVC sheet, that is, an anti-aging PVC material.

9. The method for preparing an anti-aging PVC material according to claim 8, characterized in that: The temperature of the temperature control is 160-170° C.; the mixing time is 5-7 minutes; and the thickness of the finished PVC sheet is 0.5-0.6 mm.

10. The method for preparing an anti-aging PVC material according to claim 8, characterized in that: The roller of the double-roll mill is 350 mm long and 120 mm in diameter. It is heated by oil, and the rotation speeds of the front and rear rollers are 25 rpm and 30 rpm respectively.

Citation Information

Patent Citations

  • High-tenacity anti-aging modified PVC insulation cable material

    CN104356533A

  • Heat-resistant PVC plastic and preparation method thereof

    CN112321966A

Cited By

  • A corrosion-resistant and aging-resistant PVC composite material and its preparation method

    CN122563243A